ПОЛЬСКАЯ РУСИСТИКА В ПЕРЕВОДОВЕДЧЕСКИХ ИССЛЕДОВАНИЯХ - Lewicki, Roman (Przegląd Rusycystyczny, 2016)
POLSKA RUSYCYSTYKA W BADANIACH PRZEKŁADOZNAWCZYCH Artykuł zawiera przegląd dorobku polskiej rusycystyki ostatnich dziesięcioleci w dzie-dzinie przekładoznawstwa. Punktem wyjścia jest stwierdzenie o istnieniu specyfiki badań przekładoznawczych w ramach neofilologii i odzwierciedlenia tej specyfiki w pracach polskich rusycystów poświęconych przekładowi. Zwrócono uwagę na źródła i tradycje polskiej rusycystyki w dziedzinie badań nad przekładem. Następnie omówiono rozprawy doktorskie i habilitacyjne, monografie autorskie, serie wydawnicze oraz obecność tematyki przekładoznawczej na łamach «Przeglądu Rusycystycznego». Stwierdzono wzrost zainteresowania autorów tą problematyką oraz rosnące powiązania z przekładoznawstwem uprawianym w ramach innych neofilologii. TRANSLATION STUDIES WITHIN RUSSIAN STUDIES IN POLAND This article is a survey of the achievements of translation studies as part of Russian studies in Poland over the last few decades. The author underscores the specific status of translation studies within the philology, demonstrating how this status has been reflected in the works of Polish scholars specializing in the field. He pays special attention to both the sources and traditions of translation studies carried out within Russian studies in Poland. In particular, he discusses the relevant doctoral and postdoctoral dissertations, monographs, book series, and the related issues of the Przegląd Rusycystyczny. The research shows that there has been a steady growth of interest among Polish scholars in Russian translation studies. Strong links have been found between translation studies pursued both within the Russian philology and within other language studies in Poland.